Current practices in temporal arachnoid cysts: a survey among Brazilian neurosurgeons - Raissa Mansilla; Tatiana Protzenko; Marcelo Sampaio Pousa; Clara Magalhães Paiva; Gianpiero Tamburrini; Antonio Rosa Bellas (Brazilian Society for Pediatric Neurosurgery, 2022)
Introduction: There has been no consensus for the best treatment strategy for TACs. The aim of this survey was to aggroup the different practices between Brazilian pediatric neurosurgeons in the management of a children with TAC Galassi Type II and III. Methods: contributors answered a case questionnaire about TACs and select the answer that better reflect their conduct in asymptomatic or symptomatic patients (chronic headache, epilepsy and psychomotor retardation). Results: all respondents confessed that had doubts about TACs and 59-75% was not satisfied only with brain MRI. Fundoscopy was the most required exam (28-35%),  followed by EEG/VideoEEG (19-20%), ICP-NI (16%) and MRI CSF flowmetry (12-13%). For asymptomatic, 61-85% suggested follow-up with clinical, radiologic and fundoscopic control. Still, surgery was the choice for 61-70% in symptomatic patients. The preferred technique for TAC type II was endoscopic cysto-cisternostomy (32%) and for type III craniotomy and arachnoid cyst marsupialization (25%). Discussion: Since the past 14 years, more information has become available about the natural history of TACs and innovative technologies arises for its management helps. Treatment is still debated, but endoscopy is increasingly common and proved to be safe and effective. Conclusion: modern technologies allow more security and subsidies to treatment chosen and even though for TAC Galassi type III open craniotomy still is preferred than endoscopic surgery, nowadays the least invasive treatment have been the choice for TAC Galassi Type II.  The years of experience in endoscopy and the more availability of the tool into hospitals maybe contributed to this pattern change.